Quality of Life in Patients with Idiopathic Intracranial Hypertension and the Impact of the COVID-19 Pandemic. (3rd September 2022) - Çelebisoy, Neşe; Kısabay Ak, Ayşın; Özdemir, Hüseyin Nezih; Gökçay, Figen; Eser, Erhan
ABSTRACT: The COVID-19 pandemic became a challenge to maintain care for patients with idiopathic intracranial hypertension (IIH). We aimed to find out how they were affected during lockdown. Thirty IIH patients admitted to hospital during the COVID-19 pandemic were studied. Their demographic and neuro-ophthalmological findings were evaluated. The World Health Organization – Five Well-Being Index (WHO-5), the EUROHIS Quality of Life (QOL) 8-item index, National Eye Institute Visual Functioning Questionnaire (NEI-VFQ-25), Headache Impact Test (HIT-6), and COVID-19 Fear Scale were used to assess QOL and pandemic-associated fear. Thirty age, sex, and body mass index matched volunteers constituted the control group. Apart from the COVID-19 Fear Scale and colour vision subscale of the NEI-VFQ-25, all scale scores were worse in IIH patients than in healthy control subjects. Patients with severe visual field defects had higher HIT-6 scores (p = .036). Both vision-specific and overall QOL was reduced in patients with IIH. Headache severity and disability were more prominent in patients with severe visual loss. Fear caused by the COVID pandemic was not different in IIH patients than in healthy control subjects.